PERAN KNOWLEDGE MANEGEMENT SEBAGAI MEDIASI PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Martono U; La Hatani; Sri Wiyati Mahrani (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this research is to empirically investigate the role of knowledge management as mediating on the influence of organizational culture and employee performance. The approach of this research is survey with explanatory research design. Data collection is done cross-section by using instrument in the form of questionnaire. The population of this research were 31 Civil Servants in the National Unity Board and Political of Wakatobi District except the leader (head of service). The analytical equipment used to test the hypothesis of this study is Partial least square (PLS). The results reveal that organizational culture have a significant positive influence on knowledge management. Knowledge management have a significant positive influence on employee performance. The results also indicate that organizational culture influence employee performance directly and indirectly through knowledge management is as a partial mediation. It means that, knowledge management is significantly influenced by organizational culture and knowledge management that significantly influences employee performance, then organizational culture significantly influences employee performance.Keywords: organizational culture, knowledge management, employee performance